Effect of electron irradiation on transparent conductive films ZnO:Al deposited at different sputtering power - Myroniuk, D.V.; Ievtushenko, A.I.; Lashkarev, G.V.; Maslyuk, V.T.; Timofeeva, I.I.; Baturin, V.A.; Karpenko, O.Yu.; Kuznetsov, V.M.; Dranchuk, M.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Transparent conductive oxide thin films of Al-doped ZnO grown by rf magnetron sputtering were irradiated with high energy electrons with the energy 12.6 MeV and fluence 5·10¹⁴ e/cm². The films were produced using different sputtering powers. It has been shown that electron irradiation creates defects that lead to distortions of the crystal lattice, which results in reduced crystallinity of the films. Also, it leads to film heating that results in radiation annealing and relaxation of the lattice.